2003
DOI: 10.1146/annurev.anthro.32.061002.093223
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Biology and Human Evolution

Abstract: ▪ Abstract  Our understanding of developmental biology burgeoned during the last decade. This review summarizes recent advances, provides definitions and explanations of some basic principles, and does so in a way that will aid anthropologists in understanding their profound implications. Crucial concepts, such as developmental fields, selector and realizator genes, cell signaling mechanisms, and gene regulatory elements are briefly described and then integrated with the emergence of skeletal morphology. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 115 publications
2
121
0
4
Order By: Relevance
“…In fact, Enlow (1990) noted that enthesial development is insignificant during adolescence, suggesting that mechanical strain during growth and development merely provides threshold levels for bone growth. Therefore, threshold levels set during adolescence preserve throughout adult life with mechanical strain maintaining bone strength; thus the focus is on bone retention not deposition (Lovejoy et al, 2003). Hypothetically, these observations account for deposition and resorption reduction observed in adult long bones when exposed to increased strain levels, since mechanical mechanisms are bound to predetermined threshold levels set during initial growth and development.…”
Section: Understanding Enthesesmentioning
confidence: 99%
“…In fact, Enlow (1990) noted that enthesial development is insignificant during adolescence, suggesting that mechanical strain during growth and development merely provides threshold levels for bone growth. Therefore, threshold levels set during adolescence preserve throughout adult life with mechanical strain maintaining bone strength; thus the focus is on bone retention not deposition (Lovejoy et al, 2003). Hypothetically, these observations account for deposition and resorption reduction observed in adult long bones when exposed to increased strain levels, since mechanical mechanisms are bound to predetermined threshold levels set during initial growth and development.…”
Section: Understanding Enthesesmentioning
confidence: 99%
“…As has been shown here, there appears to be no significant effect in adults of asymmetric loading of the forelimb. Persistent scars of union of fractured bones in human adults are a further indication of the lack of response of bone tissue to mechanical loading in adults [5]. Further, it has been shown that when long bone length, age and sex are fully considered, perceived populational differences in femoral cortical thickness are nonsignificant [43].…”
Section: Discussionmentioning
confidence: 99%
“…This raises the strong possibility that osteoblast response protocols are highly conserved, and do not vary substantially from one mammal to another. Such a view has also received strong support from studies of limb bud dynamics [4,5]. These suggest that differences in the structure and form of the skeleton can be traced to early initial differences in the disposition of positional information (PI).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations